An investigation into the hydrogen bond of poly (p‐phenylene benzobisoxazole)/carboxylic carbon nanotube composites, insight from quantum mechanics/molecular mechanics simulation. Issue 8 (18th April 2014) - Hu, Kun; Zhuang, Qixin; Liu, Xiaoyun; Han, Zhewen
<x xml:space="preserve">Abstract</x> Poly (p‐phenylene benzobisoxazole)/carbon nanotube (PBO/CNTs) composites have already been experimentally synthesized with the outstanding mechanical and electrical properties. Carboxylic carbon nanotubes (CNT‐COOH), obtained by acid treatment, can better disperse than pristine nanotubes in PBO matrix, which is estimated due to hydrogen bonds between them and investigated by Quantum Mechanics/Molecular mechanics (QM/MM) calculation. In the dynamic simulation, the N atoms in PBO and H atoms in carboxyl can be close enough to form hydrogen bond and the angle of oxygen–hydrogen–nitrogen (OHN) is obtuse, suitable for hydrogen bond. Further more, the electrostatic potential (ESP) and ESP fit charge of N and O atoms in PBO has been measured by Density Functional Theory (DFT) calculation to prove that hydrogen bonds can be formed only by N atoms in the heterocycle of PBO and H atoms in carboxyl of the CNT‐COOH. POLYM. COMPOS., 36:1454–1461, 2015. © 2014 Society of Plastics Engineers